Vizuální kontrola rozměrů součástí - Kadaňka, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Tato diplomová práce pojednává o porovnání průmyslového systému pro rozpoznávání objektů a měření s cenově dostupnou kamerou na platformě Raspberry Pie. V teoretické části je stručně popsáno několik metod pro měření rozměrů, které se v průmyslu běžně využívají spolu s obecným popisem technického vybavení pro záznam obrazu. V další části jsou popsány 3 průmyslové systémy pro obrazovou analýzu. Praktická část práce se zabývá návrhem měřícího standu, popisem technického vybavení, realizací měření pomocí obou platforem a následným zhodnocením.

This master thesis deals with the comparison of an industrial system for object recognition and measurement with an affordable camera on the Raspberry Pie platform. The theoretical part briefly describes several methods for measuring dimensions, which are commonly used in industry, along with a general description of technical equipment for image recording. The next section describes 3 industrial systems for image analysis. The practical part of the work deals with the design of the measuring stand, the description of the technical equipment, the implementation of measurements using both platforms and the subsequent evaluation.
Visual inspection of component dimensions
Keywords: Raspberry Pie; HQ kamera; Cognex; Python; OpenCV; NumPy; Inventor; Raspberry Pie; HQ camera; Cognex; Python; OpenCV; NumpPy; Inventor